First evidence on ergonomic exposures and musculoskeletal pain among the Faroese workforce - Rúni Bláfoss; Lars Louis Andersen; Simone Vestergaard Christiansen; Thomas Clausen; Pál Weihe; Annika Helgadóttir Davidsen (International Archives of Occupational and Environmental Health, 2026)
Objectives The Faroe Islands has historically been a fishing society, with workers being exposed to high physical work demands. However, the work environment has never been systematically studied. This study investigates associations of ergonomic exposures at work with low-back pain (LBP) and neck/shoulder pain (NSP) intensity. Methods This cross-sectional questionnaire survey included 5198 workers (∼24% of the country’s workforce), with > 3800 participants in the main analyses (∼18% of the country’s workforce). General linear models tested associations of specific ergonomic exposures and a combined ergonomic index with LBP and NSP intensity, respectively, while adjusting for relevant confounders. Results Mean LBP and NSP intensity were 2.6 (± 2.8) and 3.0 (± 2.7) points, respectively, on a 0–10 numeric rating scale. All ergonomic exposures showed strong exposure-response associations with LBP and NSP intensity, with the exception of ‘standing/walking’, which showed no significant association with NSP intensity. The strongest associations for both women and men were observed for ‘pushing/pulling’ and ‘carrying/lifting’ with LBP intensity, and ‘back bent/twisted’ and ‘pushing/pulling’ with NSP intensity. The ergonomic index (scale 0-100) showed clear exposure-response associations; women and men in the highest ergonomic demand category (> 40) reported 2.41 and 1.42 points higher LBP intensity, respectively, while all workers showed 1.51 points higher NSP intensity. Conclusions This first evidence of the ergonomic working environment in the Faroe Islands demonstrates a general working population with relatively intense pain and clear exposure-response associations between level of ergonomic demands and higher musculoskeletal pain intensity – for both women and men. Mapping these associations among the general working population in the Faroe Islands provides essential knowledge for future occupational health initiatives.

Corrective exercises administered online vs at the workplace for pain and function in the office workers with upper crossed syndrome: randomized controlled trial - Zohreh Yaghoubitajani; Mehdi Gheitasi; Mohammad Bayattork; Lars Louis Andersen (International Archives of Occupational and Environmental Health, 2022)

Work limitations due to neck-shoulder pain and physical work demands in older workers: cross-sectional study - Mohammad Bayattork; Sebastian Venge Skovlund; Emil Sundstrup; Lars Louis Andersen (International Archives of Occupational and Environmental Health, 2021)

Workplace violence and development of burnout symptoms: a prospective cohort study on 1823 social educators - Jesper Pihl-Thingvad; Ask Elklit; Lars Peter Andreas Brandt; Lars Louis Andersen (International Archives of Occupational and Environmental Health, 2019)

Electromyographic evaluation of high-intensity elastic resistance exercises for lower extremity muscles during bed rest - Jonas Vinstrup; Sebastian Skals; Joaquin Calatayud; Markus Due Jakobsen; Emil Sundstrup; Matheus Daros Pinto; Mikel Izquierdo; Yuling Wang; Mette K. Zebis; Lars Louis Andersen (European Journal of Applied Physiology, 2017)

Positive effects of 1-year football and strength training on mechanical muscle function and functional capacity in elderly men - Emil Sundstrup; Markus Due Jakobsen; Lars Louis Andersen; Thomas Rostgaard Andersen; Morten Bredsgaard Randers; Jørn Wulff Helge; Charlotte Suetta; Jakob Friis Schmidt; Jens Bangsbo; Peter Krustrup; Per Aagaard (European Journal of Applied Physiology, 2016)

Importance of mind-muscle connection during progressive resistance training - Joaquin Calatayud; Jonas Vinstrup; Markus Due Jakobsen; Emil Sundstrup; Mikkel Brandt; Kenneth Jay; Juan Carlos Colado; Lars Louis Andersen (European Journal of Applied Physiology, 2016)